Predictors of mortality in paediatric burns at ibadan, Nigeria. (2007)
Patients and Methods: This was a prospective study of children aged 0-13 years, managed in the bums unit of University College Hospital, Ibadan, Nigeria, between January 2001 and September 2003. Results: There were 62 patients, 42 (67.7%) were females and 20 (32.3%) were males (Male: Female= 1:2. Their ages ranged between 1 month and 13 years (mean = 4.8 ± 3.8 years). Majority of the patients (56.5%) were below 4 years of age. Bum was caused predominantly by flame (57%), followed by inhalation injury in 43.5% of the patients. The percentage total burn surface area (%TBSA) ranged between 1 % and 95% (mean 29.7% ± 22.8%), and 41.4% of the patients sustained a major burn (TBSA=30%). Infective complications were present in 37% of patients. The overall mortality was 33.9%, and occurred in those patients with %TBSA of 14 95% (mean = 48.8%). Mortality rate was 62.9% among those that had inhalation injury compared with 11.4% in those without inhalation injury. There was no mortality in those patients whose %TBSAranged between 1 and 32% (mean = 17.5%). Conclusion: Percentage of the total body surface area burnt and the presence of inhalation injury were important predictors of mortality in childhood bums injury.